Pembuatan Lilin Aromaterapi Dari Minyak Jelantah Bersama Ibu-Ibu Perwiritan Lingkungan II Sirandorung Kelurahan Aek Kota Batu : Penelitian - Dewi Agustina; Azkyatul Arifah Rkt; Nur Latipah Siahaan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Waste cooking oil remains a pressing issue due to low public awareness of its environmental and health impacts. Repeated use of waste oil increases the risk of degenerative diseases, while improper disposal leads to soil and water pollution. This community service program aimed to provide education and training for the mothers’ religious gathering group in Aek Kota Batu Village on utilizing waste cooking oil to produce value-added aromatherapy candles. The methods applied included socialization, demonstrations, and hands-on practice in candle making using waste cooking oil, paraffin, coloring agents, and essential oils. The results showed improved community knowledge of the hazards of waste oil as well as enhanced skills in processing it into economically valuable products. Participants demonstrated high enthusiasm, actively engaged in discussions, and were able to practice candle-making independently. This initiative not only reduced environmental pollution but also created opportunities for small-scale, eco-friendly businesses, thereby contributing to family welfare and strengthening ecological awareness in the community.